Duplex color doppler evaluation of carotid atherosclerosis in patient with silent cerebral infarction detected by MRI - Kabir, Kaniza; Quddus, MA; Haque, Rashimul; Rahman, Mizanur; Nabi, Shahryar; Rahman, Khalilur; Ahmed, Shamim; Bhowmik, Bishwajit (Journal of Dhaka Medical College, 2013)
Background: Silent cerebral infarction (SCI) detected incidentally by MRI is considered the preliminary stage of accidental stroke and assumed to be secondary to atherosclerotic vascular disease (ASVD).The Duplex Color Doppler study is the initial screening non-invasive modality to identify carotid atherosclerotic changes and is the best approach for preoperative carotid artery evaluation in asymptomatic patients who can be expected to benefit of reduced risk of stroke in future. This cross- sectional study was carried out to assess the diagnostic usefulness of Duplex Color Doppler sonography in the evaluation of asymptomatic carotid atherosclerosis in prediction of silent cerebral infarction. Nature of extracranial carotid plaque and degree of luminal stenosis were compared & associated with MRI findings and risk factors of silent cerebral infarction. Method: This cross sectional study was carried out in the Radiology & Imaging Department of Dhaka Medical College Hospital during the period of July 2009 to June 2011 on 70 adult subjects of both sexes aged >50 years. Clinically suspected patients of silent cerebral infarction referred to Radiology & Imaging department of DMCH from OPD and Indoor Patient department underwent MRI of brain and among them those diagnosed as having Lacunar infarcts (Silent Cerebral Infarction) underwent Extra-cranial Carotid Duplex Color Doppler examination on both sides. Carotid lesions were evaluated by plaque score, maximum percent stenosis and the existence of ulcerated lesions. The relations between the carotid lesions and the incidence, size or localization of the brain lesions were investigated. Results: The incidence of SCI increases with age & more prevalent in male (P<0.05).Most SCI lesions were <1cm in size, single in number and is more prevalent in basal ganglia region (P<0.05) than subcortical white matter of right cerebral hemisphere (P<0.05) associated with ipsilateral high grade carotid stenosis & ulcerated plaque. The percentage of subjects with infarcts increased significantly as the plaque score increased (P<0.001) or subjects had high grade stenosis (P<0.001). The presence of pre-existing risk factors like HTN, DM, IHD, and Dyslipidaemia showed significant correlation with plaque score and SCI of brain. Conclusion: Both the severity and characteristics of asymptomatic carotid lesions estimated by Duplex color Doppler study were closely related to the appearance of silent infarcts.These results demonstrate that noninvasive assessment of carotid lesions can be useful in predicting the existence of silent cerebral infarction even in patients free from neurological deficits. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15599 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 19-25